Uma análise com base na matriz de capacidades tecnológicas da Açúcar e Álcool Bandeirantes S.A. (Usiban/PR) - Lima, Yuri Rafael Sperotto (2024)
This article analyzes the technological dynamics of the Sugal and Alcohol Bandeirantes S.A. – Usiban/PR using the technological capabilities matrix. This approach encompasses four areas: Investment, Operation/Production, Innovation and Relations with the Economy; with three levels of technological capabilities: Basic (based on simple routines and common experience), Intermediate (based on adapting technologies) and Advanced (based on research for differentiation). As a result, Usiban's technological capabilities are not different from those found in other sugar/ethanol plants in Brazil. In other words, the presence of the Basic and Intermediate levels is common, except in the area of Operation/Production (Product Engineering profile), which, due to the sector's characteristics, is atypical for most sugar/ethanol plants in Brazil. The Advanced level was almost non-existent at Usiban/PR, except in the case of Innovation (profile Ability to Pursue Process Innovations and Development Research and Development – R&D), which is one of the important points for the technological dynamics of this plant.